Integrating conflict data for enhanced analysis: A multi-source approach to support vulnerability frameworks - Douglas, Wesley; Basel, Ashleigh; Minoarivelo, Onivola; Craparo, Alessandro; Pacillo, Grazia; Laderach, Peter (2024)
The future of conflict and food security analysis depends on moving beyond isolated datasets to embrace integrated, multi-dimensional insights. This study presents an innovative approach to integrating conflict event data from multiple sources, utilising a customised version of the Matching Event Data by Location, Time, and Type (MELTT) framework and the Validation and Exploration of the Hierarchical Integration of Conflict Event Data (VEHICLE) methodology. The analysis focuses on regions monitored by the Famine Early Warning System and Global Fragility Act priority countries, aiming to improve vulnerability frameworks within fragile regions. The resulting enhanced regional conflict datasets offer a more comprehensive understanding of conflict dynamics and are a valuable tool for organisations, supporting more effective crisis response and conflict impact assessments.